Islam in Colonial Turkestan - Sobirjon, Boltabayev (The Lingua Spectrum, 2025)
This article covers the adoption of decisions and laws against and against Islam in the territory after the colonization of the Turkestan territory by the Russian empire, keeping Islam in constant control, eliminating religious and secular education, ending schools and madrasas, nationalizing Waqf properties.